Torenia maculata (Linderniaceae), a new record for Thailand - Sutthisaksopon, Phanom; Chantaranothai, Pranom; Suddee, Somran (Thai Forest Bulletin (Botany), 2021)
Torenia maculata, is a newly recorded species for Thailand. A description, illustrations and comments on its ecology and distribution are provided.